Body Mass Index and Clinical Characteristics Among Patients Undergoing Orthopedic Implant Removal: A Retrospective Observational Study - Fouad Qupti; Nael Dabous; Waseem Jiris; Mokbil Shalah; Fadi Khalil Hanna (Orthopedic Reviews, 2026)
Objective To describe the body mass index (BMI) profile of patients who underwent orthopedic implant removal and to examine whether BMI was associated with age, sex, anatomical location, and broad symptomatic indication within the implant-removal cohort. Methods A retrospective observational analysis was conducted using clinical records of orthopedic implant removal procedures. The analytic sample included 88 implant-removal procedures performed among 78 unique patients. BMI was calculated from recorded height and weight and categorized using standard clinical thresholds. Descriptive statistics were calculated for BMI, age, sex, and anatomical location. A one-sample t-test was used to determine whether mean BMI differed significantly from the overweight threshold of 25 kg/m². Pearson and Spearman correlations were used to examine the association between age and BMI. One-way ANOVA and Kruskal-Wallis tests were used to compare BMI across age groups and anatomical regions. Fisher’s exact test was used to examine associations between high BMI, defined as BMI ≥ 25 kg/m², and weight-bearing anatomical regions. A broad symptomatic-removal variable was also examined, based on documentation of pain, irritation, prominent hardware, protruding screw, prominent metalwork, or local pressure. Statistical significance was defined as p < 0.05. Results The study included 88 implant-removal procedures among 78 patients. Mean age was 44.9 ± 16.4 years, and mean BMI was 27.33 ± 5.06 kg/m², significantly above the overweight threshold (p < 0.001). Overall, 68.2% of cases had BMI ≥ 25. BMI was not significantly associated with sex. Age showed a positive correlation with BMI (p < 0.01). BMI differed significantly across age groups and anatomical regions. High BMI was more frequent in weight-bearing regions (90.0% vs. 61.8%, p = 0.027, OR = 5.57). Broad symptomatic removal was identified in 44.3% of cases and was more common in weight-bearing anatomical sites, especially lower-extremity locations. Conclusion Patients undergoing orthopedic implant removal demonstrated a BMI profile predominantly within the overweight range, with higher BMI associated with older age and weight-bearing anatomical regions. These findings suggest that BMI may play a role in implant-related symptoms, particularly in lower-extremity sites exposed to mechanical loading. However, due to the absence of a non-removal comparison group, results should be interpreted as descriptive and hypothesis-generating rather than establishing causation.Keywords: body mass index; orthopedic implant removal; hardware removal; pain; irritation; obesity; anatomical location.